Serum proteomic changes in atopic dermatitis patients treated with cyclosporine - Jill Isabelle Olydam; Thomas Litman; Tamar Nijsten; Ilka Hoof; Witte Koopmann; Luba Milena Pardo; DirkJan Hijnen (PLoS ONE, 2026)
Background Despite significant advancements in atopic dermatitis (AD) treatment, the underlying pathogenesis remains unclear. Understanding flare and remission mechanisms is essential for understanding disease course, evaluating treatment and developing therapeutic strategies. Although biomarkers show promise for assessing disease severity, their identification, validation and clinical utility demand further research. Objectives To investigate inflammatory changes involved in AD flares and remissions, we studied changes in expression of 368 circulating biomarkers during cyclosporine (CsA) treatment. Methods The study included 40 AD patients experiencing a disease flare and starting CsA treatment. Serum samples were collected at baseline, after 2 and 4 weeks of treatment. Results CsA treatment induced a rapid improvement of disease severity and reduced proteins related to Th2, Th1 and Th17 pathways. Four novel markers, FKBP1B, PDLIM7, MAP2K6 and EIF4G1 demonstrated decreased expression levels after treatment. In addition, CCL17/TARC and OX40 levels showed a strong correlation with disease severity. Interestingly, NME3, SMOC2, and GAL showed increased expression after treatment. We identified four biomarkers that may be linked to the pathogenesis of flares and remissions. Lastly, we identified OX40 as a potential biomarker for disease severity. Conclusion We identified four novel serum biomarkers possibly related to treatment effect and we identified OX40 as a potential serum biomarker for assessing disease severity. These findings enhance understanding of AD pathogenesis and offer tools for monitoring therapeutic response and disease severity.